Conjunctival Stromal Tumor: Report of 2 New Cases and Review of the Literature. (May 2021) - Lam, Jonathan; Ang, Andrea; Vermeulen, Tersia; Ardakani, Nima Mesbah
Conjunctival stromal tumor (COST) is an emerging entity with only a limited number of cases reported in the literature. In this report, we describe 2 additional cases, review the accumulative clinical and histopathological features and expand on the immunophenotypic property of this entity. COST appears to have a sporadic presentation, affecting both sexes and patients of variable ethnicity and age group and predominantly occurring on the bulbar conjunctiva as a slow-growing asymptomatic or slightly tender mass-like lesion. Histopathologically, COST is characterized by singly dispersed spindle to round cells, often with some degree of degenerative nuclear atypia, within a myxomatous to collagenous stroma. Lesional cells are characteristically positive for CD34 and vimentin, negative for S100, SOX10 and STAT6 and show a normal pattern of staining with RB1 by immunohistochemistry. The reported cases to date have shown an indolent biological behavior, reliably treated by a complete surgical excision.